2020
DOI: 10.5539/ijel.v10n2p80
|View full text |Cite
|
Sign up to set email alerts
|

How Social Support and Foreign Language Anxiety Impact Willingness to Communicate in English in an EFL Classroom

Abstract: This study investigates the impact of social support and foreign language anxiety (FLA) on learners’ willingness to communicate (WTC) in English (L2) inside the classroom in an EFL context of Pakistan. The study administered adapted questionnaires on willingness to communicate (WTC), social support and foreign language anxiety (FLA) to 200 undergraduates of University of Balochistan, Quetta, Pakistan. To analyse the data, both descriptive and inferential statistics were performed in the SPSS. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The findings are in line with previous research. For instance, Kalsoom et al (2020) found that the participants in her study received more social support from their friends, whereas the support from mothers and siblings was negligible for communicating in English in class. The informants were not encouraged by mothers and siblings on WTC in English.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The findings are in line with previous research. For instance, Kalsoom et al (2020) found that the participants in her study received more social support from their friends, whereas the support from mothers and siblings was negligible for communicating in English in class. The informants were not encouraged by mothers and siblings on WTC in English.…”
Section: Discussionmentioning
confidence: 85%
“…The participants used less English language with their neighbours and friends. Nevertheless, previous research showed that friends play an essential role in engendering learners' WTC (Ali, 2017;Jung, 2011;Kalsoom et al, 2020;MacIntyre et al, 2001;Mari et al, 2011). Ali (2017) found that Pakistani learners had more WTC with their friends than with acquaintances and strangers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying English in Pare make them separate with family and friend. Support from Family and siblings were not correlated significantly (Kalsoom et al, 2020). This condition make them only get support from teacher and other friends, the people who could meet the most while they are living in Kampung Inggris.…”
Section: The Correlation Between Efl Students' Willingness To Communicate and Social Supportmentioning
confidence: 85%
“…Where the global village extends its areas and relations of teaching and learning from internal to external connections i.e. the support of father, mother, teachers, friends, classmates, public and media to support and appreciate learners' willingness to communicate in English (Kalsoom, Soomro & Pathan, 2020) to increase and enhance the motivation and confidence (Fallah, 2014). The importance of English language cannot be ignored due to someone's physical, personal, psychological and sociological status and contribution (Varela, Polo, Garcia & Mertinez, 2010) towards the growth and development of the world and humanity to maintain peace and prosperity, which is considered as sociopolitical demand (Mansoor, 2003).…”
Section: A English In Global Perspectivesmentioning
confidence: 99%